The Ontological Implications of Spirit Encounters. Issue 3 (1st September 2019) - Barnes, Jamie
Abstract : This article offers a reflexive and phenomenological response to some of the challenges of the recent ontological turn. It argues, first, that a focus on embodiment is crucial in understanding the formation of ontological assumptions, and, second, that researchers have an ethical responsibility to practice an 'ontological reflexivity' that goes beyond the conceptual reflexivity of much recent ontological work. It conceives the anthropological domain as a place of 'intra-actment' and maintains that to avoid ontological closure, researchers must contextualize their ontological assumptions by reflexively sensitizing themselves to how these assumptions are shaped by both embodied experience and the contexts in which they are articulated and performed. This article seeks to enact this through an auto-ethnographic exploration of the author's own embodied experience as it relates to demonic manifestations and the divine.